Essays on Turkish literature and history - Flemming, Barbara. (Middle East and Islamic Studies E-Books Online, Collection 2018, ISBN: 9789004353343., 2018)
In Essays on Turkish Literature and History Barbara Flemming makes available essays partly previously published in German. They offer insights gained through decades of scholarship. Although the Ottoman period is central, a wide range is covered, including an early Turkish principality, Mamluk and Ottoman Egypt, and contemporary southeastern Turkey. The essays look into historical and political factors involved in the preoccupation with the world's ending, into Muslim-Christian dialogue, the sultan's prayer before battle, and the bilingualism of poets. Of particular interest are the sections on female participation in mysticism, on an anti-Sufi movement in Cairo, on the Ottoman capital's appeal to collectors and emigrants (Diez, Süssheim, Böhlau), and on the far-reaching effects of alphabet change.